2013
DOI: 10.1093/mnras/stt1529
|View full text |Cite
|
Sign up to set email alerts
|

Physical parameters and the projection factor of the classical Cepheid in the binary system OGLE-LMC-CEP-0227

Abstract: A novel method of analysis of double-lined eclipsing binaries containing a radially pulsating star is presented. The combined pulsating-eclipsing light curve is built up from a purely eclipsing light curve grid created using an existing modeling tool. For every pulsation phase the instantaneous radius and surface brightness are taken into account, being calculated from the disentangled radial velocity curve of the pulsating star and from its out-of-eclipse pulsational light curve and the light ratio of the com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 44 publications
(51 reference statements)
8
75
0
Order By: Relevance
“…The uncertainty of p was computed from the combination of the error bars of the independent measurements of OGLE-LMC-CEP-0227 (P = 3.80 d, p = 1.21 ± 0.05, Pilecki et al 2013), δ Cep (P = 5.37 d, p = 1.288 ± 0.054, Mérand et al 2015), and the present measurement of RS Pup (P = 41.5 d, p = 1.250 ± 0.064). We did not average the error bars of the different p-factor measurements from the HST/FGS distances as the degree of correlation between them and the possible associated systematics are uncer- Pilecki et al (2013) and Gieren et al (2015), and we selected only the best p-factor of δ Cep derived by Mérand et al (2015). In agreement with the present results, Breitfelder et al (2016) also concluded from a fit to the complete sample of measured p-factors that a constant value of p = 1.324 ± 0.024 (1σ from our value) reproduces the measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainty of p was computed from the combination of the error bars of the independent measurements of OGLE-LMC-CEP-0227 (P = 3.80 d, p = 1.21 ± 0.05, Pilecki et al 2013), δ Cep (P = 5.37 d, p = 1.288 ± 0.054, Mérand et al 2015), and the present measurement of RS Pup (P = 41.5 d, p = 1.250 ± 0.064). We did not average the error bars of the different p-factor measurements from the HST/FGS distances as the degree of correlation between them and the possible associated systematics are uncer- Pilecki et al (2013) and Gieren et al (2015), and we selected only the best p-factor of δ Cep derived by Mérand et al (2015). In agreement with the present results, Breitfelder et al (2016) also concluded from a fit to the complete sample of measured p-factors that a constant value of p = 1.324 ± 0.024 (1σ from our value) reproduces the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Even for distant Cepheids, however, whose angular diameters cannot be measured directly, the robustness of the SPIPS algorithm will enable an accurate calibration of their physical properties, including the p-factor, once their parallaxes are known. (Benedict et al 2002(Benedict et al , 2007, the orange points are the LMC eclipsing Cepheids (Pilecki et al 2013;Gieren et al 2015). The solid line and orange shaded area represent the weighted average p = 1.293 ± 0.039.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used RaveSpan (Pilecki et al 2012(Pilecki et al , 2013 to measure the radial velocities of both stars in the system using the broadening function (BF) formalism (Rucinski 1992(Rucinski , 1999. We used templates from the library of synthetic LTE spectra by Coelho et al (2005) matching the mean values of estimated effective temperature and gravity of the stars in the binary.…”
Section: Radial Velocitiesmentioning
confidence: 99%
“…The 'non-spotted' sample contains 14 LMC and SMC systems (Graczyk et al 2012;Pietrzyński et al 2013;Pilecki et al 2013;Graczyk et al 2014), KIC 8410673 (Frandsen et al 2013), AI Phe (Andersen et al 1988;He lminiak et al 2009), TZ For (Andersen et al 1991), OW Gem (Ga lan et al 2008), α Aur (Torres et al 2009(Torres et al , 2015, CF Tau (Lacy et al 2012), V432 Aur (Siviero et al 2004), HD187669 (He lminiak et al 2015), ASAS J180057-2333.8, (Suchomska et al 2015), ASAS J182510-2435.5 (Ratajczak et al 2013), and two more systems we have analysed but not published yet (ASAS-061, V64). We want to note, that the 'non-spotted' systems may also be active, but the activity level must be lower than for the 'spotted' ones, as there is no clear sign of variability in the published photometry, usually more precise than the ASAS data.…”
Section: Giants With and Without Spots In Eclipsing Binariesmentioning
confidence: 99%